On the atomic decomposition length of graphs and tensegrities - Fernández-Rodríguez, Jose David; Orden Martín, David (My University, 2013)
In this study, a complexity measure for graphs and tensegrities is proposed, based on the concept of atomic decomposition.We state several results on the relationship between atomic decompositions and spaces of self-stresses for generically rigid graphs, and study the computational complexity of ﬁnding atomic decompositions of minimal length.
Keywords: Matemáticas computacionales; Tensegrity; Tensegrity atom; Atomic decomposition